Corporate Social Irresponsibility, Profitabilitas dan Reputasi Perusahaan - Rawi Rawi; Tri Neliana; Rina Destiana (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
This study will explain how corporate social irresponsibility and profitability affect corporate reputation. This study aims to obtain empirical evidence on the influence of corporate social irresponsibility and profitability on corporate reputation. The data used is secondary data in the form of annual reports and sustainability reports from companies in the Basic Materials sector listed on the Indonesia Stock Exchange from 2022 to 2024. The research approach used in this study is the quantitative method. The sampling method used in this study is purposive sampling, a sampling technique determined based on the researcher's consideration of certain criteria. The sample used in this study consisted of 66 samples. The analysis method used in this study was logistic regression. The results of the study showed that corporate social irresponsibility had a negative effect on corporate reputation, while profitability had a positive effect on corporate reputation.